Dietary Omega-3 Oil Supplementation To Increase Omega-3 Polyunsaturated Fatty Acids In The Red Tilapia(Oreochromis Hybrid) And Catfish (Clarias Gariepinus) - Mar Mar Kyi, (2007)

(untitled)
A study was carried out to determine the essential polyunsaturated fatty acid (PUFA) profiles of the red tilapia (Oreochromis hybrid) and catfish (Clarias gariepinus) and an attempt was made to increase the omega-3 polyunsaturated fatty acids by dietary omega -3 oil supplementation. The fatty acid profiles of commercially farmed adult fish were determined using standard extraction, fatty acid methylation and gas liquid chromatographic procedures and the fatty acid concentration of dried fish tissues was expressed in absolute amounts (mg/g) as a measure of the actual fatty acid content in the fish tissues. The levels of total fatty acids, SFA, UFA, monoenes, total n-6, total n-3, 18:2n-6 and 18:3n-3 were higher in the catfish compared to the red tilapia. The higher (17-20% of the total fatty acids) n-6 PUFA found in both fish compared to n-3 PUFA (1.0 – 9.5 %) was characteristic for freshwater fish. The absolute amounts of total n-6 and n-3 PUFA increased as the age of the fish increased for both species of fish when measured from 10 to 75 days of age although they decreased when expressed as a percentage of total fatty acids. The absolute amounts of total n-6 PUFA in the red tilapia increased from 10.0 ± 0.6 mg/g at 10 days to 26.6 ± 2.4 mg/g at 75 days of age. The absolute amounts of total n-3 PUFA in the red tilapia increased from 3.6 ± 0.2 mg/g at 10 days to 9.4 ± 0.3 mg/g at 75 days of age. Similarly, the absolute amounts of total n-6 PUFA in the catfish increased from 15.1 ±1.0 mg/g at 10 days to 36.5 ± 2.5 mg/g at 75 days of age whilst the absolute amounts of total n-3 PUFA increased from 8.1 ± 0.2 mg/g at 10 days to 21.8 ± 1.5 mg/g at 75 days of age. The results were suggestive of a combined effect of accumulation, desaturation and elongation and oxidation of the PUFA in the fish tissues. The Δ6 desaturase enzyme activity in the liver microsomes was measured in six of each species of fish employing radiolabelled linoleic acid [1-14C] and argentation thin layer chromatography. Desaturase activities were detected in both species but the activity in the red tilapia (3.55 + 0.2%; 1.19 + 0.1 pmol/min/mg protein) was higher, although not significant (p>0.05), than the catfish (3.07 ± 0.2%; 1.02 + 0.1 pmol/min/mg protein). The antioxidant enzymes, superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) and the lipid peroxidation value of malonaldehyde (MDA) were measured in ten of each species of fish. The antioxidant activity was higher in the catfish whilst the lipid peroxidation value was higher in the red tilapia. The activity of SOD (1.54 ± 0.1 U/g) and GSH-Px (0.37 ± 0.1 U/g) in the red tilapia was lower than the activity of SOD (2.48 ± 0.1 U/g) and GSH-Px (1.18 ± 0.1 U/g) in the catfish. The MDA values were 21.39 ± 0.5 nmol/g for the red tilapia compared to 19.15 ± 0.2 nmol/g for the catfish. The dietary omega-3 oil supplementation trial was carried out for eight weeks where the fish was reared in glass aquariums in under three dietary treatments, in triplicate. The treatment diets were the control diet CON (with no oil added), or diets containing added 10% or 20% flaxseed oil (10% FLAX or 20% FLAX) or added 10% or 20% cod-liver oil (10% COD, 20% COD). The desirable n-3 PUFA were not increased by the 10% FLAX or 10% COD diets where the total n-3 PUFA concentrations in the red tilapia were 3.2 + 0.1 mg/g (CON), 2.6 ± 0.2 mg/g (10% FLAX) and 3.4 ± 0.2 mg/g (10% COD). The n-3 PUFA concentrations in the catfish were 7.1 ± 0.4 mg/g (CON), 6.4 ± 0.1 mg/g (10% FLAX) and 6.4 ± 0.4 mg/g (10%COD). However, the n-3 PUFA concentrations were significantly increased (p<0.05) when fed the 20% FLAX and 20% COD diets. In the red tilapia the n-3 PUFA concentrations were 3.4 ± 0.1 mg/g (CON), 4.7 ± 0.1 mg/g (20% FLAX) and 3.8 ± 0.2 mg/g (20% COD). The n-3 PUFA concentrations in the catfish were 6.5 ± 0.3 mg/g (CON), 8.5 ± 0.6 mg/g (20% FLAX) and 9.0 ± 0.6 mg/g (20% COD). However high mortality rates up to 60% were encountered when the 20% FLAX and 20% COD diets were used suggesting that the levels of the oils used in these diets were toxic to the fish. Histological examinations carried out at post-mortem confirmed the toxicological condition by the occurrence of several histopathological lesions in the liver, kidney and small intestine. In conclusion, the essential PUFA profiles of the red tilapia which has a herbivorous mode of nutrition and the catfish which is more omnivorous, with different desaturase and oxidative enzyme activities are somewhat different, where the former represents a better source of desirable essential PUFA to the human consumer. The concentrations of the desirable essential PUFA in both fishes can be increased by modifying their diets to contain added oils such as flaxseed or cod-liver oil but the percentage of the added oils have to be between 10-20% of the diet to avoid toxicity and high mortalities.